The Hidden Cost of Insurance on Cooperation. (5th September 2017) - van de Calseyde, Philippe P.F.M.; Keren, Gideon; Zeelenberg, Marcel
Abstract: A common solution to mitigate risk is to buy insurance. Employing the trust game, we find that buying insurance against the risk of betrayal has a hidden cost: trustees are more likely to act opportunistically when trustors choose to be insured against the breach of trust. Supposedly, trustees are less likely to cooperate when trustors buy insurance because choosing insurance implicitly signals that the trustor expects the trustee to behave opportunistically, paradoxically encouraging trustees not to cooperate. These results shed new light on the potential drawbacks of financial safeguards that are intended to minimize the risky nature of trust taking: the presumed safeguard against the risk of betrayal may, under certain circumstances, increase the probability of betrayal. Copyright © 2017 John Wiley & Sons, Ltd.